Exploring the usage of supervised driving automation in naturalistic conditions. (October 2022) - Stapel, Jork; Happee, Riender; Christoph, Michiel; van Nes, Nicole; Martens, Marieke
Highlights: A naturalistic dataset comparing manual and SAE2 automated driving was enriched with automation status and driver attention. Effects of road type, driving speed, time of day, trip duration and experience on automation use were examined. Automation was used around 60% of time on highways and was rarely activated on roads with speed limits below 70 km/h. Automation use increased with time in trip while showing minor changes with time of day and automation experience. Automation use and automation experience showed small but significant effects on head pose variance, indicating subtle changes in monitoring strategies. Abstract: This study reports usage of supervised automation and driver attention from longitudinal naturalistic driving observations. Automation inexperienced drivers were provided with instrumented vehicles with adaptive cruise control (ACC) and lane keeping (LK) features (SAE level 2). Data was collected comparing one month of driving without support to two months where drivers were instructed to use automation as desired. On highways, level 2 automation was used respectively 63% and 57% of the time by Tesla and BMW users, with peak usage during slow stop-and-go traffic (0–30 km/h) and higher speeds (>80 km/h). On roads with speed limits below 70 km/h, automation was used less than 8%, and use on urban roads was incidental rather than habitual. Automation usage increased with time in trip, but no clear time of day effects were found. Head pose data could not classify driver attention, and we recommend gaze tracking in future studies. Head pose deviation was selected as alternative indicator for monitoring activity. Comparing among forms of automation usage on the highway, head heading deviation was smallest during ACC use, but did not differ between automation and baseline manual driving. Head heading deviation during manual driving was smaller in the baseline than the experimental phase, which suggests that motives for manual highway driving may be attention related. Automation usage did not change much over the first 12 weeks of the experimental condition, and there were no longitudinal changes in head pose deviation.